Answer:
x = - 2
Explanation:
The 9 does absolutely nothing. Multiply the whole equation by. 9. Remember that each term must show the 9 is missing
(5x + 10)^2 - x(25x + 27) + 46 = 0
Next expand the first and second binomial so that the brackets can be removed.
(25x^2 + 100x + 100) - (25x^2 + 27x) + 46 = 0
Now remove the brackets
25x^2 + 100x + 100 - 25x^2 - 27x + 46 = 0
Collect the like terms
25x^2 - 25x^2 + 100x - 27x + 100 +46 = 0
73x + 146 = 0
Subtract 146 from both sides
73x = - 146
Divide by 73
x = - 146/73
x = - 2 <<<< Answer